Respuesta :
Answer:
hi
Step-by-step explanation:
We see a set of linear equations. Hence, a system of linear equations. So we solve them by process of elimination, multiplying the top equation by 5 to eliminate first such that
(2x+y=20)*5
6x-5y=12
-----------------------------------------
10x+5y=100
6x-5y=12
--------------------------------
16x = 112 .............After dividing 16 we get
x = 7
Now we plug x = 7 back into the original first equation to obtain the y value such that
2(7) + y = 20
12 + y = 20
-12 -12
------------------
y = 8
I hope this helped!
(-2x + 10) - (-6x + 5y + 12) + (x + 8y - 16)
=(-2*5 + 10) - (-6*5 + 5*-4 + 12) + (5 + 8*-4 - 16)
= (-10 + 10) - (-30 - 20 + 12) + (5 -32 - 16)
= 0 - (-38) + (-43)
= 38 - 43
= -5
=(-2*5 + 10) - (-6*5 + 5*-4 + 12) + (5 + 8*-4 - 16)
= (-10 + 10) - (-30 - 20 + 12) + (5 -32 - 16)
= 0 - (-38) + (-43)
= 38 - 43
= -5